(untitled) (World Economics and Finance Bulletin, 2022)
Small business and private entrepreneurship is one of the important drivers of economic development, increasing employment and incomes of the population. In order to support the subjects of this sphere in recent years, more than 50 decrees and resolutions of the President of the Republic of Uzbekistan have been adopted